Mikuláš Bek, Geoffrey Chew and Petr Macek ed.: Socialist realism and music, Colloquium Musicologicum Brunense, 36, 2001, Institute of Musicology, Faculty of Arts, Masaryk University Brno, Koniasch Latin Press, Praha, 2004: Socijalistički realizam i muzika, Muzikološki kolokvijum u Brnu, zbornik radova (MUZIKOLOGIJA-MUSICOLOGY, 2025)
Book Review